Patterns and Determinants of Compliance with Inhaled Steroids in Adults with Asthma - Yves Lacasse; Hélène Archibald; Pierre Ernst; Louis-Philippe Boulet (Canadian Respiratory Journal)
BACKGROUND: Patient compliance with inhaled corticosteroids (ICS) in asthma is considered to be suboptimal.